Walnut shell graded porous activated charcoal as well as preparation method and application thereof
By using walnut shells to prepare graded porous activated biochar, the problems of insufficient performance and high production cost of biochar electrode materials in the prior art are solved, and the preparation and environmentally friendly production process of high-performance electrode materials are realized.
Patent Information
- Application Number
- CN202411632631.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-14
- Publication Date
- 2025-02-07
AI Technical Summary
The existing biochar and electrochemical new energy storage materials have problems such as high raw material costs, difficult material pore structure, insufficient electrochemical performance, complex production process, large environmental impact and high cost of supercapacitors.
Walnut shells are used as raw materials to prepare graded porous activated biochar by oxygen-limiting cracking method, combining KOH activator and pyrolysis treatment to accurately regulate the pore structure of the carbon material and improve electrochemical performance.
The high-value utilization of biomass waste is achieved, the specific capacitance and rate performance of electrode materials is improved, the preparation process is simplified, the production cost is reduced, and the environmental impact is reduced.
Smart Images

Figure CN119390068A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of biochar and electrochemical new energy storage materials, and in particular to a walnut shell graded porous activated biochar and a preparation method and application thereof. Background Art
[0002] It is pointed out in the relevant technology that biochar, as a kind of finger-repellent material obtained by pyrolysis of biomass under anaerobic or hypoxic conditions, has gradually become a research hotspot due to its cheap and readily available raw materials, abundant reserves, and environmental friendliness. At the same time, biochar has great potential in energy storage devices such as supercapacitors due to its high specific surface area and good chemical stability. As a new type of energy storage device, supercapacitors have attracted attention for their high power density, long cycle life, and fast charging and discharging capabilities. They can provide higher power density than traditional capacitors, with simple structure and high reliability. Low maintenance cost. Applying biochar to supercapacitors can produce new energy storage devices with high energy density, high power density, long life and environmental friendliness, which have broad application prospects in renewable energy storage, electric vehicles, portable electronic devices and other fields.
[0003] At present, the technical problems existing in biochar and electrochemical new energy storage materials mainly include the following aspects:
[0004] 1. Raw material cost and sustainability issues: Traditional electrode materials may rely on expensive or unsustainable resources, which not only increases the cost of the final product but may also have a negative impact on the environment.
[0005] 2. Material pore structure control: The new energy of supercapacitors depends largely on the pore structure of electrode materials. Existing technologies make it difficult to accurately control the size and distribution of pores, which affects the penetration of electrolytes and the transmission efficiency of ions.
[0006] 3. Electrochemical properties of electrode materials: In energy storage devices such as supercapacitors, the specific capacitance and rate performance of electrode materials are key indicators. Existing technologies fail to provide materials that can maintain specific capacitance at high current density, thus limiting the energy density and power density of device ideas.
[0007] 4. Complexity and efficiency of the production process: Traditional electrode material preparation processes can be complex, time-consuming and costly.
[0008] 5. Environmental impact and waste of resources: Existing technologies do not fully consider the environmental impact during the production process, or fail to effectively utilize biomass waste, resulting in certain impacts on the environment.
[0009] 6. Supercapacitor cost issue: The cost of supercapacitors is affected by electrode materials, production process and other factors, resulting in high costs. Summary of the invention
[0010] The present invention aims to solve at least one of the technical problems existing in the prior art. To this end, the present invention provides a walnut shell graded porous activated biochar and a preparation method and application thereof, which can improve the performance of super carbon electrode materials and reduce their costs.
[0011] To achieve the above-mentioned object of the invention, the present invention provides a method for preparing walnut shell graded porous activated biochar, comprising the following steps:
[0012] S1 Preparation of walnut shell raw materials: immerse the walnut shell in a mixed solution of ethanol and deionized water, perform ultrasonic cleaning for 13-17 minutes, remove impurities on the surface of the walnut shell, crush the cleaned walnut shell through a 45-55 mesh sieve, and place in a drying oven at 75°C-85°C for 23h-25h;
[0013] S2 Preparation of walnut shell biochar: The crushed walnut shell obtained in step S1 is placed in a crucible, and then placed in a tube furnace for pre-carbonization. After the pre-carbonization is completed, it is naturally cooled to room temperature, and the product is taken out and ground through a 45-55 mesh sieve to obtain walnut shell biochar;
[0014] Preparation of S3 activator: Grind KOH solid and pass through 45-55 mesh sieve;
[0015] S4 preparation of a mixture of walnut shell biochar and an activator: directly mix the walnut shell biochar obtained in step S2 and the activator obtained in step S3 according to a set ratio, stir evenly to obtain a mixture of walnut shell biochar and an activator, and set aside;
[0016] S5 Preparation of graded porous activated biochar from walnut shells: put the mixture obtained in step S4 into a crucible, place the crucible in a tubular furnace for pyrolysis, and naturally cool to room temperature after the pyrolysis. Take out the product and wash it repeatedly with 0.8mol / L-1.2mol / L hydrochloric acid and deionized water in sequence until it is neutral, so that the pores of the carbon material are fully exposed, and transfer it to a drying oven at 75℃-85℃ for 11h-13h to obtain graded porous activated biochar from walnut shells.
[0017] In some embodiments, the mixing ratio of ethanol to deionized water in the mixed solution of step S1 of the present invention is 1:2.
[0018] In some embodiments, the pre-carbonization conditions of step S2 of the present invention are: heating rate of 4°C / min-6°C / min, pyrolysis temperature of 450°C-550°C, pyrolysis time of 1.8h-2.2h, nitrogen flow rate of 115sccm-125sccm; after the above reaction is completed, naturally cool to room temperature, take out the product and grind it through a 45-55 mesh sieve.
[0019] In some embodiments, the pyrolysis conditions of step S5 of the present invention are: heating rate of 3°C / min-7°C / min, pyrolysis temperature of 800°C-900°C, pyrolysis time of 1.8h-2.2h, and nitrogen flow rate of 115sccm-125sccm.
[0020] In order to achieve the above-mentioned purpose of the invention, the present invention also provides a walnut shell graded porous activated biochar, which is prepared by the above-mentioned preparation method.
[0021] To achieve the above-mentioned purpose of the invention, the present invention also provides a method for preparing an electrode material, comprising weighing the above-mentioned walnut shell graded porous activated biochar, acetylene black and PTFE according to a set mass ratio; first, dissolving PTFE in alcohol for later use; then, placing the walnut shell graded porous activated biochar powder and acetylene black in an agate mortar, grinding and mixing them thoroughly, then dropping a PTFE alcohol mixed solution, grinding and mixing them thoroughly to obtain a mixture, which is a walnut shell graded porous activated biochar electrode material.
[0022] In some embodiments, the present invention uses a CHI660E electrochemical tester to test the electrochemical performance of the electrode material, using a standard three-electrode configuration, wherein the reference electrode is a Hg / HgO electrode, the counter electrode is a platinum electrode, the working electrode is an electrode modified with walnut shell graded porous activated biochar, and the electrolyte is 100ml 6mol / L KOH solution.
[0023] Compared with the prior art, it has the following beneficial effects:
[0024] 1) High-value utilization of biomass waste: The present invention uses walnut shells, a biomass waste, as raw material and converts it into high-performance electrode materials through oxygen-limited pyrolysis, which not only realizes the resource utilization of waste, but also improves the economic value of biomass.
[0025] 2) Innovative application of oxygen-limited pyrolysis method: The pre-carbonization process of the present invention is carried out under a nitrogen atmosphere, and the oxygen-limited pyrolysis technology is used to effectively control the carbonization reaction, avoid excessive oxidation, and ensure the high carbon content and good conductivity of the biochar, which is crucial to the performance of the electrode material.
[0026] 3) Precise regulation of hierarchical porous structure: The present invention can precisely regulate the pore structure of biochar through high-temperature pyrolysis after uniform mixing with KOH solid, forming a rich hierarchical porous structure, which is conducive to the penetration of electrolyte and the rapid transmission of ions, thereby improving the electrochemical performance of electrode materials.
[0027] 4) Simple and efficient preparation process: The preparation method of the present invention is simple to operate, has a short process, and has a high conversion efficiency from walnut shells to the final graded porous carbon biochar, which is beneficial to reducing production costs and improving production efficiency.
[0028] 5) Dual advantages of environmental friendliness and cost-effectiveness: Using biomass waste as raw materials not only reduces pollution to the environment, but also reduces the production cost of materials, making new energy storage equipment such as supercapacitors more economical and practical.
[0029] 6) Excellent electrochemical properties: The graded porous carbon walnut shell graded porous activated biochar prepared by the method of the present invention has excellent electrochemical properties, which has broad application prospects in energy storage devices such as supercapacitors and helps promote the development of new energy storage technology.
[0030] Additional aspects and advantages of the present invention will be given in part in the following description and in part will be obvious from the following description, or will be learned through practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 is a method flow chart of the method for preparing walnut shell graded porous activated biochar according to the present invention;
[0032] Figure 2 It is a microtubule structure diagram of the graded porous activated biochar from walnut shells of the present invention, wherein Figure (a) is a microtubule structure diagram of Example 1; Figure (b) is a microtubule structure diagram of Example 2; Figure (c) is a schematic diagram of the microtubule structure of Example 3; Figure (d) is a schematic diagram of the microtubule structure of Example 4; Figure (e) is a microstructure diagram of Example 5; Figure (f) is a schematic diagram of the microtubule structure of Example 6; and Figure (g) is a microstructure diagram of Comparative Example 1.
[0033] Figure 3 3 and 4. The cyclic voltammetric characteristic curves of the walnut shell graded porous activated biochar electrode material of the present invention are shown in FIG. 3 , FIG. 3 is a cyclic voltammetric characteristic curve of Example 1; FIG. 3 is a cyclic voltammetric characteristic curve of Example 2; FIG. 3 is a cyclic voltammetric characteristic curve of Example 3; FIG. 3 is a cyclic voltammetric characteristic curve of Example 4; FIG. 3 is a cyclic voltammetric characteristic curve of Example 5; FIG. 3 is a cyclic voltammetric characteristic curve of Example 6; and FIG. 3 is a cyclic voltammetric characteristic curve of Comparative Example 1.
[0034] Figure 4 2 is a cyclic voltammetric characteristic curve diagram of the walnut shell graded porous activated biochar electrode material according to the present invention, wherein Figure (a) is a constant current charge and discharge characteristic curve diagram of Example 1; Figure (b) is a constant current charge and discharge characteristic curve diagram of Example 2; Figure (c) is a constant current charge and discharge characteristic curve diagram of Example 3; Figure (d) is a constant current charge and discharge characteristic curve diagram of Example 4; Figure (e) is a constant current charge and discharge characteristic curve diagram of Example 5; Figure (f) is a constant current charge and discharge characteristic curve diagram of Example 6; Figure (g) is a constant current charge and discharge characteristic curve diagram of Comparative Example 1. DETAILED DESCRIPTION
[0035] Embodiments of the present invention are described in detail below, examples of which are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements having the same or similar functions. The embodiments described below with reference to the accompanying drawings are exemplary and are intended to be used to explain the present invention, and should not be construed as limiting the present invention.
[0036] The disclosure below provides many different embodiments or examples to realize different structures of the present invention. In order to simplify the disclosure of the present invention, the parts and settings of specific examples are described below. Of course, they are only examples, and the purpose is not to limit the present invention. In addition, the present invention can repeat reference numbers and / or letters in different examples. This repetition is for the purpose of simplicity and clarity, and does not itself indicate the relationship between the various embodiments and / or settings discussed. In addition, the examples of various specific processes and materials provided by the present invention, but those of ordinary skill in the art can be aware of the applicability of other processes and / or the use of other materials.
[0037] Example 1 (WBC1)
[0038] The method for preparing walnut shell graded porous activated biochar of the present invention comprises the following steps:
[0039] S1 Preparation of walnut shell raw materials: immerse the walnut shell in a mixed solution of ethanol and deionized water, perform ultrasonic vibration cleaning for 13 minutes, remove impurities on the surface of the walnut shell, crush the cleaned walnut shell through a 45-mesh sieve, and place it in a drying oven at 75°C for 23 hours; wherein the mixing ratio of ethanol to deionized water in the mixed solution is 1:2;
[0040] S2 Preparation of walnut shell biochar: Put the crushed walnut shell obtained in step S1 into a crucible, and then place it in a tube furnace for pre-carbonization. The pre-carbonization conditions are: heating rate of 4°C / min, pyrolysis temperature of 450°C, pyrolysis time of 2.2h, nitrogen flow rate of 115sccm; After the above reaction is completed, cool naturally to room temperature, take out the product and grind it through a 45-mesh sieve. After the pre-carbonization is completed, cool naturally to room temperature, take out the product and grind it through a 45-mesh sieve to obtain walnut shell biochar;
[0041] Preparation of S3 activator: Grind KOH solid and pass through 45 mesh sieve;
[0042] S4 Preparation of a mixture of walnut shell biochar and an activator: 5 g of the walnut shell biochar obtained in step S2 and 5 g of the KOH solid obtained in step S3 are directly mixed in a ratio of 1:1, and stirred evenly to obtain a mixture of walnut shell biochar and an activator, which is set aside;
[0043] S5 Preparation of graded porous activated biochar from walnut shells: put the mixture obtained in step S4 into a crucible, and place the crucible in a tubular furnace for pyrolysis. The pyrolysis conditions are: heating rate of 3°C / min, pyrolysis temperature of 800°C, pyrolysis time of 2.2h, nitrogen flow rate of 115sccm. After the pyrolysis is completed, naturally cool to room temperature. After the product is taken out, it is repeatedly washed with 0.8mol / L hydrochloric acid and deionized water in sequence until it is neutral, so that the pores of the carbon material are fully exposed, and then transferred to a drying oven at 75°C for 13h to obtain graded porous activated biochar from walnut shells. The obtained graded porous activated biochar from walnut shells is labeled as WBC1.
[0044] A method for preparing an electrode material based on WBC1, comprising the following steps: weighing 24 mg of WBC1 powder, 3 mg of acetylene black and 3 mg of PTFE in a mass ratio of 8:1:1, dissolving PTFE in 1 ml of alcohol and setting aside; then, placing the WBC1 powder and acetylene black in an agate mortar, grinding and mixing them thoroughly, then dropping a PTFE alcohol mixed solution, grinding and mixing them thoroughly to obtain a mixture, which is a walnut shell graded porous activated biochar electrode material.
[0045] In order to detect the electrochemical performance of the electrode material, the electrode material was used to prepare the electrode sheet for testing. The preparation method is as follows: 20g of walnut shell graded porous activated biochar electrode material was mixed into a dough shape, rolled into a pancake shape on a stainless steel plate with a glass rod, and then applied to the surface of the nickel foam. Then, it was placed in a tablet press, and a 1MPa pressure was added. After pressing for 10 seconds, it was taken out and placed in an 80°C drying oven for drying overnight to obtain a test electrode sheet, which was marked as WBC1 electrode sheet. The additional pressure, pressing time and drying oven temperature can also be selected according to actual conditions. For example, the additional pressure can be 0.8MPa, 0.9MPa, 1.1MPa or 1.2MPa, the pressing time can be 8s, 9s, 11s or 12s, and the drying oven temperature can be 75°C, 76°C, 78°C, 81°C, 82°C or 84°C.
[0046] The electrochemical properties of the electrode sheet were tested. By testing the electrochemical properties of the electrode sheet, the electrochemical properties of the electrode material can be learned. The test method is as follows: CHI660E electrochemical tester was used for testing, and a standard three-electrode configuration was adopted, wherein the reference electrode was a Hg / HgO electrode, the counter electrode was a platinum electrode, the working electrode was an electrode modified with walnut shell graded porous activated biochar, and the electrolyte was 100ml 6mol / L KOH solution.
[0047] The test results of WBC1 electrode are as follows: the specific surface area is 1157.78m 2 ·g -1 ; Micropore surface area is 1084.61m 2 ·g -1 ; Total pore volume is 0.46cm 3 ·g -1 ; Micropore volume is 0.41cm 3 ·g -1 The average pore size is 2.5 nm, and the micropore surface area accounts for 93.68% of the total specific surface area. At a current density of 0.25 A / g, the specific capacitance is 161.75 F·g -1 ; The electrochemical performance was improved by 51.5%.
[0048] Example 2 (WBC2)
[0049] The preparation method of walnut shell graded porous activated biochar in this embodiment is as follows:
[0050] S1 Preparation of walnut shell raw materials: immerse the walnut shells in a mixed solution of ethanol and deionized water, and perform ultrasonic vibration cleaning for 14 minutes to remove impurities on the surface of the walnut shells. Crush the cleaned walnut shells through a 47-mesh sieve and place them in a 77°C drying oven for 23.5 hours. The mixing ratio of ethanol to deionized water in the mixed solution is 1:2.
[0051] S2 Preparation of walnut shell biochar: The crushed walnut shell obtained in step S1 is placed in a crucible, and then placed in a tube furnace for pre-carbonization. The pre-carbonization conditions are: heating rate of 4.5°C / min, pyrolysis temperature of 470°C, pyrolysis time of 1.9h, nitrogen flow rate of 117sccm; After the above reaction is completed, it is naturally cooled to room temperature, and the product is taken out and ground through a 47-mesh sieve. After the pre-carbonization is completed, it is naturally cooled to room temperature, and the product is taken out and ground through a 47-mesh sieve to obtain walnut shell biochar;
[0052] Preparation of S3 activator: Grind KOH solid and pass through 47 mesh sieve;
[0053] S4 Preparation of a mixture of walnut shell biochar and an activator: 5 g of the walnut shell biochar obtained in step S2 and 10 g of the KOH solid obtained in step S3 are directly mixed in a ratio of 1:2, and stirred evenly to obtain a mixture of walnut shell biochar and an activator, which is set aside;
[0054] S5 Preparation of graded porous activated biochar from walnut shells: Put the mixture obtained in step S4 into a crucible, and place the crucible in a tubular furnace for pyrolysis. The pyrolysis conditions are: heating rate of 4°C / min, pyrolysis temperature of 820°C, pyrolysis time of 1.9h, and nitrogen flow rate of 117sccm. After the pyrolysis is completed, cool naturally to room temperature, take out the product and wash it repeatedly with 0.9mol / L hydrochloric acid and deionized water until it is neutral, so that the pores of the carbon material are fully exposed, and transfer it to a drying oven at 77°C for 11.5h to obtain graded porous activated biochar from walnut shells. The obtained graded porous activated biochar from walnut shells is labeled WBC2;
[0055] The electrode material was prepared based on WBC2, and the preparation method was the same as that in Example 1;
[0056] Based on the above electrode materials, an electrode sheet for testing was prepared using the same preparation method as in Example 1 to obtain a WBC2 electrode sheet.
[0057] The electrochemical performance of the WBC2 electrode sheet was tested using the same test method as in Example 1. The test results are as follows: The specific surface area is 1944.71 m 2 ·g -1 ; Micropore surface area is 1748.76m 2 ·g -1 ; Total pore volume is 0.80cm 3 ·g -1 ; Micropore volume is 0.68cm 3 ·g -1 The average pore size is 2.72 nm. At a current density of 0.25 A / g, the specific capacitance is 232 F·g -1 ; The electrochemical performance increased by 116.39%.
[0058] Example 3 (WBC3)
[0059] refer to Figure 1 As shown, the preparation method of walnut shell graded porous activated biochar in this embodiment is as follows: Figure 1 As shown, the specific method is as follows:
[0060] S1 Preparation of walnut shell raw materials: immerse the walnut shells in a mixed solution of ethanol and deionized water, and perform ultrasonic cleaning for 15 minutes to remove impurities on the surface of the walnut shells. Crush the cleaned walnut shells through a 50-mesh sieve and place them in a drying oven at 80°C for 24 hours. The mixing ratio of ethanol to deionized water in the mixed solution is 1:2.
[0061] S2 Preparation of walnut shell biochar: Put the crushed walnut shell obtained in step S1 into a crucible, and then place it in a tube furnace for pre-carbonization. The pre-carbonization conditions are: heating rate of 5°C / min, pyrolysis temperature of 500°C, pyrolysis time of 2h, nitrogen flow rate of 120sccm; After the above reaction is completed, cool naturally to room temperature, take out the product and grind it through a 50-mesh sieve. After the pre-carbonization is completed, cool naturally to room temperature, take out the product and grind it through a 50-mesh sieve to obtain walnut shell biochar;
[0062] Preparation of S3 activator: Grind KOH solid and pass through a 50-mesh sieve;
[0063] S4 Preparation of a mixture of walnut shell biochar and an activator: 5 g of the walnut shell biochar obtained in step S2 and 15 g of the KOH solid obtained in step S3 are directly mixed in a ratio of 1:3, and stirred evenly to obtain a mixture of walnut shell biochar and an activator, which is set aside;
[0064] S5 Preparation of graded porous activated biochar from walnut shells: Put the mixture obtained in step S4 into a crucible, place the crucible in a tube furnace for pyrolysis, and the pyrolysis conditions are: heating rate of 5°C / min, pyrolysis temperature of 850°C, pyrolysis time of 2h, and nitrogen flow rate of 120sccm. After the pyrolysis is completed, cool naturally to room temperature, take out the product and wash it repeatedly with 1mol / L hydrochloric acid and deionized water until it is neutral, so that the pores of the carbon material are fully exposed, and transfer it to a drying oven at 80°C for 12h to obtain graded porous activated biochar from walnut shells. The obtained graded porous activated biochar from walnut shells is labeled WBC2;
[0065] The electrode material was prepared based on WBC3, and the preparation method was the same as that in Example 1;
[0066] Based on the above electrode materials, an electrode sheet for testing was prepared using the same preparation method as in Example 1 to obtain a WBC3 electrode sheet.
[0067] The electrochemical performance of the WBC3 electrode sheet was tested using the same test method as in Example 1. The test results are as follows: the specific surface area is 2387.13 m 2 ·g -1 ; Micropore surface area is 1767.35m 2 ·g -1 ; Total pore volume is 1.03cm 3 ·g -1 ; Micropore volume is 0.70cm 3 ·g -1 The average pore size is 2.38 nm. At a current density of 0.25 A / g, the specific capacitance is 287.5 F·g -1 ; The electrochemical performance increased by 169.32%.
[0068] Example 4 (WBC4)
[0069] The preparation method of walnut shell graded porous activated biochar in this embodiment is as follows:
[0070] S1 Preparation of walnut shell raw materials: immerse the walnut shells in a mixed solution of ethanol and deionized water, and perform ultrasonic vibration cleaning for 15.5 minutes to remove impurities on the surface of the walnut shells. Crush the cleaned walnut shells through a 52-mesh sieve and place them in a drying oven at 82°C for 24.5 hours. The mixing ratio of ethanol to deionized water in the mixed solution is 1:2.
[0071] S2 Preparation of walnut shell biochar: Put the crushed walnut shell obtained in step S1 into a crucible, and then place it in a tube furnace for pre-carbonization. The pre-carbonization conditions are: heating rate of 5.5℃ / min, pyrolysis temperature of 552℃, pyrolysis time of 2.1h, nitrogen flow rate of 122sccm; After the above reaction is completed, cool naturally to room temperature, take out the product and grind it through a 52-mesh sieve. After the pre-carbonization is completed, cool naturally to room temperature, take out the product and grind it through a 52-mesh sieve to obtain walnut shell biochar;
[0072] Preparation of S3 activator: Grind KOH solid and pass through 52 mesh sieve;
[0073] S4 Preparation of a mixture of walnut shell biochar and an activator: 2 g of the walnut shell biochar obtained in step S2 and 8 g of KOH solid obtained in step S3 are directly mixed in a ratio of 1:4, and stirred evenly to obtain a mixture of walnut shell biochar and an activator, which is set aside;
[0074] S5 Preparation of graded porous activated biochar from walnut shells: Put the mixture obtained in step S4 into a crucible, place the crucible in a tube furnace for pyrolysis, and the pyrolysis conditions are: heating rate of 6°C / min, pyrolysis temperature of 860°C, pyrolysis time of 1.9h, and nitrogen flow rate of 122sccm. After the pyrolysis is completed, cool naturally to room temperature, take out the product and wash it repeatedly with 1.1mol / L hydrochloric acid and deionized water until it is neutral, so that the pores of the carbon material are fully exposed, and transfer it to a drying oven at 82°C for 12.5h to obtain graded porous activated biochar from walnut shells. The obtained graded porous activated biochar from walnut shells is labeled WBC4;
[0075] The electrode material was prepared based on WBC4, and the preparation method was the same as that in Example 1;
[0076] Based on the above electrode materials, an electrode sheet for testing was prepared using the same preparation method as in Example 1 to obtain a WBC4 electrode sheet.
[0077] The electrochemical performance of the WBC4 electrode sheet was tested in the same manner as in Example 1. The test results are as follows: the specific surface area is 2480.33 m 2 ·g -1 ; Micropore surface area is 1792.22m 2 ·g -1 ; Total pore volume is 1.08cm 3 ·g -1 ; Micropore volume is 0.71cm 3 ·g -1 The average pore size is 2.30 nm. At a current density of 0.25 A / g, the specific capacitance is 398.0 F·g -1 ; The electrochemical performance increased by 272.83%.
[0078] Example 5 (WBC5)
[0079] The preparation method of walnut shell graded porous activated biochar in this embodiment is as follows:
[0080] S1 Preparation of walnut shell raw materials: immerse the walnut shells in a mixed solution of ethanol and deionized water, and perform ultrasonic vibration cleaning for 16 minutes to remove impurities on the surface of the walnut shells. Crush the cleaned walnut shells through a 54-mesh sieve and place them in a drying oven at 83°C for 24 hours. The mixing ratio of ethanol to deionized water in the mixed solution is 1:2.
[0081] S2 Preparation of walnut shell biochar: Put the crushed walnut shell obtained in step S1 into a crucible, and then place it in a tube furnace for pre-carbonization. The pre-carbonization conditions are: heating rate of 5°C / min, pyrolysis temperature of 480°C, pyrolysis time of 2h, nitrogen flow rate of 120sccm; After the above reaction is completed, naturally cool to room temperature, take out the product and grind it through a 54-mesh sieve. After the pre-carbonization is completed, naturally cool to room temperature, take out the product and grind it through a 54-mesh sieve to obtain walnut shell biochar;
[0082] Preparation of S3 activator: Grind KOH solid and pass through 54 mesh sieve;
[0083] S4 Preparation of a mixture of walnut shell biochar and an activator: 2 g of the walnut shell biochar obtained in step S2 and 8 g of KOH solid obtained in step S3 are directly mixed in a ratio of 1:4, and stirred evenly to obtain a mixture of walnut shell biochar and an activator, which is set aside;
[0084] S5 Preparation of graded porous activated biochar from walnut shells: put the mixture obtained in step S4 into a crucible, place the crucible in a tube furnace for pyrolysis, and the pyrolysis conditions are: heating rate of 6.5℃ / min, pyrolysis temperature of 800℃, pyrolysis time of 2h, and nitrogen flow rate of 120sccm. After the pyrolysis is completed, cool naturally to room temperature, take out the product and wash it repeatedly with 1.2mol / L hydrochloric acid and deionized water until it is neutral, so that the pores of the carbon material are fully exposed, and transfer it to a drying oven at 78℃ for 12h to obtain graded porous activated biochar from walnut shells. The obtained graded porous activated biochar from walnut shells is labeled WBC5;
[0085] The electrode material was prepared based on WBC5, and the preparation method was the same as that in Example 1;
[0086] Based on the above electrode material, an electrode sheet for testing was prepared using the same preparation method as in Example 1 to obtain a WBC5 electrode sheet.
[0087] The electrochemical performance of the WBC5 electrode sheet was tested using the same test method as in Example 1. The test results are as follows: the specific surface area is 3445.37 m 2 ·g -1 ; Micropore surface area is 419.06m 2 ·g -1 ; Total pore volume is 1.63cm 3 ·g -1 ; Micropore volume is 0.09cm 3 ·g -1 The average pore size is 2.23 nm. At a current density of 0.25 A / g, the specific capacitance is 281 F·g -1 ; The electrochemical performance is improved by 163.32%.
[0088] Example 6 (WBC6)
[0089] The preparation method of walnut shell graded porous activated biochar in this embodiment is as follows:
[0090] S1 Preparation of walnut shell raw materials: immerse the walnut shells in a mixed solution of ethanol and deionized water, and perform ultrasonic cleaning for 17 minutes to remove impurities on the surface of the walnut shells. Crush the cleaned walnut shells through a 55-mesh sieve and dry them in a drying oven at 85°C for 23 hours. The mixing ratio of ethanol to deionized water in the mixed solution is 1:2.
[0091] S2 Preparation of walnut shell biochar: Put the crushed walnut shell obtained in step S1 into a crucible, and then place it in a tube furnace for pre-carbonization. The pre-carbonization conditions are: heating rate of 6°C / min, pyrolysis temperature of 550°C, pyrolysis time of 1.8h, nitrogen flow rate of 125sccm; After the above reaction is completed, cool naturally to room temperature, take out the product and grind it through a 55-mesh sieve. After the pre-carbonization is completed, cool naturally to room temperature, take out the product and grind it through a 55-mesh sieve to obtain walnut shell biochar;
[0092] Preparation of S3 activator: Grind KOH solid and pass through 55 mesh sieve;
[0093] S4 Preparation of a mixture of walnut shell biochar and an activator: 2 g of the walnut shell biochar obtained in step S2 and 8 g of KOH solid obtained in step S3 are directly mixed in a ratio of 1:4, and stirred evenly to obtain a mixture of walnut shell biochar and an activator, which is set aside;
[0094] S5 Preparation of graded porous activated biochar from walnut shells: Put the mixture obtained in step S4 into a crucible, place the crucible in a tube furnace for pyrolysis, and the pyrolysis conditions are: heating rate of 7°C / min, pyrolysis temperature of 900°C, pyrolysis time of 2h, and nitrogen flow rate of 125sccm. After the pyrolysis is completed, cool naturally to room temperature, take out the product and wash it repeatedly with 1.2mol / L hydrochloric acid and deionized water until it is neutral, so that the pores of the carbon material are fully exposed, and transfer it to a drying oven at 85°C for 11h to obtain graded porous activated biochar from walnut shells. The obtained graded porous activated biochar from walnut shells is labeled WBC6;
[0095] The electrode material was prepared based on WBC6, and the preparation method was the same as in Example 1;
[0096] Based on the above electrode material, an electrode sheet for testing was prepared using the same preparation method as in Example 1 to obtain a WBC6 electrode sheet.
[0097] The electrochemical performance of the WBC6 electrode sheet was tested in the same manner as in Example 1. The test results are as follows: the specific surface area is 2359.42 m 2 ·g -1; Micropore surface area is 267.61m 2 ·g -1 ; Total pore volume is 1.90cm 3 ·g -1 ; Micropore volume is 0.02cm 3 ·g -1 The average pore size is 2.36 nm. At a current density of 0.25 A / g, the specific capacitance is 157.65 F·g -1 ; The electrochemical performance increased by 47.68%.
[0098] Comparative Example 1 (WBC0)
[0099] In this comparative example, the electrode material and electrode sheet are prepared by using the existing corn straw biochar. The preparation method is the same as that in Example 1 to obtain a WBC0 electrode sheet. The electrochemical performance of the electrode sheet is tested in the same way as in Example 1. The test results are as follows: the specific surface area is 115.38 m 2 ·g -1 ; Micropore surface area is 112.23m 2 ·g -1 ; Total pore volume is 0.80cm 3 ·g -1 ; Micropore volume is 0.05cm 3 ·g -1 The average pore size is 39.18 nm. At a current density of 0.25 A / g, the specific capacitance is 106.75 F·g -1 , the electrochemical performance was improved by 47.68%.
[0100] Refer to Table 1, which shows the preparation conditions of the walnut shell graded porous activated biochar prepared in Examples 1-6 and Comparative Example 1, the test results of the performance of the walnut shell graded porous activated biochar and the walnut shell graded porous activated biochar electrode material:
[0101] Table 1 Preparation conditions of materials in the examples and comparative examples and results of performance tests of the prepared materials
[0102]
[0103]
[0104] As can be seen from the above table, with the change of carbon-alkali ratio, activation pyrolysis temperature and activation pyrolysis time, the performance of the walnut shell graded porous activated biochar prepared by the present invention is significantly improved. Specifically, the electrochemical properties of the walnut shell graded porous activated biochar and its electrode material prepared in Examples 1-6 of the present invention are compared with the corn straw biochar and biochar electrode material of Comparative Example 1 from the following aspects:
[0105] ①Specific surface area
[0106] The specific surface area of comparative example 1 is 115.38 m 2 ·g -1 In Examples 1-6 of the present invention, the specific surface area is increased to a minimum of 1157.78 m 2 ·g -1 (Example 1), increased by 9.03 times; the highest increased to 3529.42m 2 ·g -1 (Example 6), an increase of 29.69 times. The increase in specific surface area provides the walnut shell graded porous activated biochar with more pores and surface active sites, thereby improving the conductivity of the electrode, accelerating the rate of electron transfer, and significantly improving its adsorption capacity for pollutants.
[0107] ②Micropore surface area
[0108] The micropore surface area of Comparative Example 1 is 112.23 m 2 ·g -1 In Examples 1-6 of the present invention, the micropore surface area is increased to 1792.22 m 2 ·g -1 (Example 4), increased by 9.62 times, the minimum increased to 267.61m 2 ·g -1 (Example 6), an increase of 1.38 times. The increase in micropore surface area increases the specific capacitance of walnut shell graded porous activated biochar, optimizes ion transport and adsorption, enhances electrochemical performance, increases energy density and power density, and improves electrolyte penetration. These effects work together to significantly improve the performance of the electrode material.
[0109] ③Total pore volume
[0110] The total pore volume of Comparative Example 1 is 0.08 cm 3 ·g -1 In Examples 1-6 of the present invention, the total pore volume is increased to 1.90 cm 3 ·g -1 (Example 6), increased by 22.75 times, the minimum increased to 0.46cm 3 ·g -1 (Example 1), an improvement of 4.75 times.
[0111] ④Average pore size, specific capacitance and performance improvement
[0112] The average pore size of comparative example 1 is 39.18 nm, while the average pore size of embodiments 1-6 of the present invention is 2.23 nm-2.72 nm. The average pore size is reduced, the macropores are reduced, the micropores are increased, and the specific capacitance performance is greatly improved.
[0113] Specifically, the electrochemical properties of the biochar and walnut shell graded porous activated biochar electrode sheets obtained in Examples 1-6 of the present invention and the biochar and biochar electrode materials of Comparative Example 1 were analyzed in terms of specific capacitance and performance improvement: the specific capacitance of Comparative Example 1 was 106.75 F·g -1 Compared with Comparative Example 1, the specific capacitance of Examples 1-6 is increased to 398.0 F·g -1 (Example 4), the minimum is increased to 157.65F·g -1 (Example 6), the performance was improved by 272.83% (Example 4) at the highest, and 47.68% (Example 6) at the lowest. It can be seen from the above data that the walnut shell graded porous activated biochar and electrode material prepared by the present invention, compared with the comparative example 1, have increased energy density, improved electrochemical performance, improved cycle stability, enhanced rate characteristics, improved conductivity, and optimized ion transmission, etc., and effectively improved the electrochemical performance of the electrode material.
[0114] In summary, compared with the comparative example, the electrochemical properties of the walnut shell graded porous activated biochar and electrode material prepared by the method of the present invention are significantly improved in the embodiments of the present invention, and the conversion efficiency and service life of the electrode material are effectively improved.
[0115] refer to Figure 2 The microstructure of the walnut shell graded porous activated biochar obtained in Examples 1-6 and Comparative Example 1 is shown in FIG. 1. The amount of activating agent in Examples 1-4 of the present invention increases successively. As the amount of activating agent increases, the specific surface area increases from 1157.78 m 2 ·g-1 gradually increases to 2480.33m 2 g-1, indicating that the number of micropores gradually increases, refer to Figure 2 As shown in Figures (a) to (d), the pore size distribution is clear and uniform, and mesopores and macropores are gradually formed. The specific capacitance of Examples 1-4 is also increased from 161.75 F·g-1 to 398 F·g-1, and the specific capacitance performance is increased from 51.5% to 272.83%. It can be seen that the carbon-base ratio plays a vital role in the electrochemical performance of the walnut shell graded porous activated biochar of the present invention.
[0116] In Example 5 and Example 6 of the present invention, the walnut shell graded porous activated biochar prepared under the preparation conditions shown in Table 1 has a specific surface area of 3445.37 m 2 ·g -1 and 3529.41m 2 ·g -1 , its micropore surface area is only 419.6m 2 ·g -1 and 267.61m 2 ·g -1The total pore volume is increased from 0.08 in comparative example 1 to 1.63 and 1.90, respectively. Meanwhile, the average pore size of Example 5 and Example 6 is reduced from 39.18 in comparative example 1 to 2.30 and 2.23, respectively. The walnut shell graded porous activated biochar prepared in Example 5 and Example 6, as shown in Figure (e) and Figure (f) in reference figure (2), has significantly more micropores than the biochar prepared in comparative example 1, as shown in Figure (g) in reference figure (2). Therefore, the specific capacitance performance of Example 5 and Example 6 is improved by 163.32% and 47.68%, respectively, compared with that of comparative example 1.
[0117] And reference Figure 2 As shown in Figure (g), no clear pores were formed in Comparative Example 1 (the specific surface area was only 115.38 m 2 ·g -1 , most of them), the performance is poor, the conductivity and electron transfer rate of the electrode material are low, and the adsorption capacity of pollutants is poor.
[0118] In summary, the walnut shell graded porous activated biochar electrode material prepared in Examples 1-6 improves the electrochemical properties of the electrode material, accelerates the rate of electron transfer, significantly improves its adsorption capacity for pollutants, optimizes ion transport and adsorption, enhances electrochemical performance, improves energy density and power density, and improves electrolyte penetration, etc. These effects work together to significantly improve the performance of the electrode material.
[0119] refer to Figure 3 The cyclic voltammetric characteristic curves of the biochar electrode materials prepared in Examples 1-6 and Comparative Example 1 are shown. Figure 3 As shown in Figure (e), the cyclic voltammetric characteristic curve of comparative example 1 is approximately triangular, with an asymmetric shape up and down, indicating that the electrode reaction has poor reversibility and low charge transfer efficiency during the charging process, which will lead to short cycle life, poor rate performance, and low energy efficiency.
[0120] The cyclic voltammetric characteristic curves of the activated biochar prepared in Examples 1-6 are all obviously reversible rectangular-shaped, indicating that they have typical double-layer capacitance behavior and good electrochemical stability, thereby providing high power density and enabling the capacitor to charge and discharge quickly. Figure 3 In addition, the biochar prepared in Examples 1-6 not only improves the cycle life, but also reduces the impact on the environment due to its environmentally friendly characteristics.
[0121] refer to Figure 4As shown in Figures (a) to (f) in the figure, the discharge time can be seen from the constant current charge and discharge characteristic curves corresponding to Examples 1-6, which shows that the electrode sheets of Examples 1-6 have a large capacity, and also show that the battery has a high energy density and a strong charge storage potential, because it can store and release more energy at the same current. Figure 4 As shown in Figure (g), it can be seen that the discharge time is relatively Figure 4 Figures (a) to (f) are significantly reduced, indicating that the energy storage of the electrode material of Comparative Example 1 is worse than that of Examples 1-6.
[0122] In summary, the walnut shell graded porous activated biochar electrode material prepared from the walnut shell graded porous activated biochar of the present invention has good electrochemical properties and high stability. Therefore, the capacitor prepared from the walnut shell graded porous activated biochar electrode material of the present invention can effectively increase the storage capacity of the capacitor and improve the power density of the capacitor. At the same time, it can adapt to a wider operating temperature range, thereby being suitable for more usage environments.
[0123] In the description of the present invention, it should be understood that the terms "center", "longitudinal", "lateral", "length", "width", "thickness", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside", "clockwise", "counterclockwise", "axial", "radial", "circumferential" and the like indicate orientations or positional relationships based on the orientations or positional relationships shown in the accompanying drawings, and are only for the convenience of describing the present invention and simplifying the description, and do not indicate or imply that the referred device or element must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as limiting the present invention.
[0124] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features. In the description of the present invention, the meaning of "plurality" is two or more, unless otherwise clearly and specifically defined.
[0125] In the present invention, unless otherwise clearly specified and limited, the terms "installed", "connected", "connected", "fixed" and the like should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection, an electrical connection, or a communication; it can be a direct connection, or an indirect connection through an intermediate medium, it can be the internal connection of two elements or the interaction relationship between two elements. For ordinary technicians in this field, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.
[0126] In the present invention, unless otherwise clearly specified and limited, a first feature being "above" or "below" a second feature may mean that the first and second features are in direct contact, or the first and second features are in indirect contact through an intermediate medium. Moreover, a first feature being "above", "above" or "above" a second feature may mean that the first feature is directly above or obliquely above the second feature, or simply means that the first feature is higher in level than the second feature. A first feature being "below", "below" or "below" a second feature may mean that the first feature is directly below or obliquely below the second feature, or simply means that the first feature is lower in level than the second feature.
[0127] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.
[0128] Although the embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the claims and their equivalents.
Claims
1. A method for preparing walnut shell graded porous activated biochar, characterized in that: The following steps are involved: S1 Preparation of walnut shell raw materials: immerse the walnut shell in a mixed solution of ethanol and deionized water, perform ultrasonic cleaning for 13-17 minutes, remove impurities on the surface of the walnut shell, crush the cleaned walnut shell through a 45-55 mesh sieve, and place in a drying oven at 75°C-85°C for 23h-25h; S2 Preparation of walnut shell biochar: The crushed walnut shell obtained in step S1 is placed in a crucible, and then placed in a tube furnace for pre-carbonization. After the pre-carbonization is completed, it is naturally cooled to room temperature, and the product is taken out and ground through a 45-55 mesh sieve to obtain walnut shell biochar; Preparation of S3 activator: Grind KOH solid and pass through 45-55 mesh sieve; S4 preparation of a mixture of walnut shell biochar and an activator: directly mix the walnut shell biochar obtained in step S2 and the activator obtained in step S3 according to a set ratio, stir evenly to obtain a mixture of walnut shell biochar and an activator, and set aside; S5 Preparation of graded porous activated biochar from walnut shells: put the mixture obtained in step S4 into a crucible, place the crucible in a tubular furnace for pyrolysis, and naturally cool to room temperature after the pyrolysis. Take out the product and wash it repeatedly with 0.8mol / L-1.2mol / L hydrochloric acid and deionized water in sequence until it is neutral, so that the pores of the carbon material are fully exposed, and transfer it to a drying oven at 75℃-85℃ for 11h-13h to obtain graded porous activated biochar from walnut shells.
2. The method for preparing walnut shell graded porous activated biochar according to claim 1, characterized in that: The mixing ratio of ethanol to deionized water in the mixed solution of step S1 is 1:
2.
3. The method for preparing walnut shell graded porous activated biochar according to claim 1, characterized in that: The pre-carbonization conditions of step S2 are: heating rate of 4°C / min-6°C / min, pyrolysis temperature of 450°C-550°C, pyrolysis time of 1.8h-2.2h, nitrogen flow rate of 115sccm-125sccm; after the above reaction is completed, naturally cool to room temperature, take out the product and grind it through a 45-55 mesh sieve.
4. The method for preparing walnut shell graded porous activated biochar according to claim 1, characterized in that: The pyrolysis conditions of step S5 are: heating rate of 3°C / min-7°C / min, pyrolysis temperature of 800°C-900°C, pyrolysis time of 1.8h-2.2h, and nitrogen flow rate of 115sccm-125sccm.
5. A walnut shell graded porous activated biochar, characterized in that: The method is prepared according to any one of claims 1 to 4.
6. A method for preparing an electrode material, characterized in that: The walnut shell graded porous activated biochar, acetylene black and PTFE according to claim 5 are weighed according to a set mass ratio; first, the PTFE is dissolved in alcohol and set aside, then, the walnut shell graded porous activated biochar powder and acetylene black are placed in an agate mortar, and are fully ground and mixed, and then the PTFE alcohol mixed solution is added dropwise, and the mixture is fully ground and mixed to obtain a mixture, which is a walnut shell graded porous activated biochar electrode material.
7. The method for preparing an electrode material according to claim 6, characterized in that: The electrochemical performance of the electrode material was tested using a CHI660E electrochemical tester with a standard three-electrode configuration, in which the reference electrode was a Hg / HgO electrode, the counter electrode was a platinum electrode, the working electrode was an electrode modified with walnut shell graded porous activated biochar, and the electrolyte was 100 ml of 6 mol / L KOH solution.
Citation Information
Cited By
Electro-adsorption desalting electrode coating material and preparation method of coated electrode
CN120817656A